Análise da capacidade antiviral de azoestilbenoides frente ao vírus sindical respiratório - Cortés, Margarita Alexandra Peña (2017)
Respiratory syncytial virus (RSV) is a highly contagious viral agent and the most common respiratory diseases of lower tract being one of the major causes of morbidity and mortality in children, elderly and immunocompromised. Treatment includes supportive therapy and ribavirin. However, antiviral therapies are expensive, difficult to administer and are not proven to be effective. The aim of this study was to investigate in vitro the antiviral activity of three azo compounds synthesized from the structural alteration of the modified resveratrol stilbene in MRC-5 and A549 cells against RSV infection. The effect of compounds REDRESV 01, REDRESV 02 and REDRESV 03 on cell viability, inhibitory concentration, cytopathic reduction activity and virucidal activity were evaluated by MTT assay. Data showed that REDRESV 01 is cytotoxic for both cell lines showing IC50 58.6μM (MRC-5) and 17.43μM (A549). The study was followed only with the compounds REDRESV 02 (MRC-5 = 87.58μM and A549 = 40.73μM) and REDRESV 03 (MRC-5 = 150.1μM and A549 = 43.44μM) because of the higher IC50 values. Data indicated that the low percentages of inhibition on viral replication were not promising in the search for new antiviral drugs since compounds tested were not able to maintain a significantly viable number of cells during infection. However, in post-infection treatment REDRESV 02 and REDRESV 03 showed selectivity at concentration of 20 μM for the tumor cell (A549) when infected. Both compounds decreased viability twice of the infected A549 cell as compared to the viral control. Compounds also showed a possible virucidal activity which may indicate besides having a cytotoxic effect on tumor cells they may still inactivate the circulating particles when cells are infected. Although the compounds have shown promising results for the treatment of cancer patients infected with RSV new studies should be conducted to investigate other types of virus and other types of cancer, as well as the mechanisms involved in this process.